NUEVA ESPECIE DE ORMISCODES PARA CHILE (LEPIDOPTERA: SATURNIIDAE) - Beéche C., Marcos A. (Acta Entomológica Chilena, 2022)
Ormiscodes raquelae sp. nov. of Satumiidae is described from Southern Chile. This species is distinctive from the other members of Ormiscodes Blanchard for the maculation and color of the wings and the genitalia. Adults, genitalia and antenna of both sexes are illustrated